2016
DOI: 10.3390/s17010050
|View full text |Cite
|
Sign up to set email alerts
|

Literature Review: Theory and Application of In-Line Inspection Technologies for Oil and Gas Pipeline Girth Weld Defection

Abstract: Girth weld cracking is one of the main failure modes in oil and gas pipelines; girth weld cracking inspection has great economic and social significance for the intrinsic safety of pipelines. This paper introduces the typical girth weld defects of oil and gas pipelines and the common nondestructive testing methods, and systematically generalizes the progress in the studies on technical principles, signal analysis, defect sizing method and inspection reliability, etc., of magnetic flux leakage (MFL) inspection,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(44 citation statements)
references
References 58 publications
(60 reference statements)
0
33
0
1
Order By: Relevance
“…They are always the weak points of the pipelines due to the field joining and worsened laying locations because of limited right-of-way. GW defects of newly built pipelines are much narrower, which challenges the traditional ILI technologies and analyzing methods when detecting, and are more dangerous because of higher diameters and pressures [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…They are always the weak points of the pipelines due to the field joining and worsened laying locations because of limited right-of-way. GW defects of newly built pipelines are much narrower, which challenges the traditional ILI technologies and analyzing methods when detecting, and are more dangerous because of higher diameters and pressures [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…To meet the rapidly growing demand for oil and gas, the construction of trunk pipelines which can operate in high-pressure, high-speed and high-capacity conditions has been increasing in recent years, giving the pipelines larger diameters, thicker pipe walls, deeper burial depths and larger transportation distances [2,3,4,5]. Due to corrosion and high-pressure loadings on the pipe wall, pipeline failures including defects, deformations, blockages, leakages and explosions occur every year, resulting in serious risks to pipeline safety [6,7,8]. In China, it was reported that there was a pipeline failure every 4 km [9], and in the USA, the economic and human losses due to the significant pipeline incidents in the past 20-year period are $7 billion and 330 fatalities along with 1292 injuries, respectively [10].…”
Section: Introductionmentioning
confidence: 99%
“…The problem of missing sample points of information increases when the PIG runs inside concave and convex pipe sections like pipe elbows [21] because they are the pipeline sections where corrosion is most likely to occur due to fluid stagnation [22]. In addition, the missing echoes affect the post-processing techniques applied to the thickness mesh construction (many post-processing techniques interpret each pipe wall thickness acquired as one pixel of an image) [12,23,24,25,26]. Therefore, the reliability of the fault detection falls until the detection capacity is not admissible (80% being the minimum acceptable value according to international standards [4,5]).…”
Section: Introductionmentioning
confidence: 99%